Detection and molecular characterization of diarrhea causing viruses in single and mixed infections in children: A comparative study between Bangladesh and Turkey. Issue 7 (16th September 2013) - Mitui, Marcelo Takahiro; Bozdayi, Gulendam; Ahmed, Selim; Matsumoto, Takashi; Nishizono, Akira; Ahmed, Kamruddin
Abstract The incidence and mortality caused by diarrhea differ among countries. The prevalence of different enteric viruses, their molecular characteristics, and infections with multiple viruses might affect the disease incidence and mortality caused by diarrhea. The objective of this study was to determine the distribution and molecular characteristics of enteric viruses in children with diarrhea in Turkey and Bangladesh. A total of 288 stool samples that were negative for group A rotavirus were collected from children aged <5 years with acute diarrhea who presented to hospitals in Turkey and Bangladesh. The samples were screened for human bocavirus (HBoV), astrovirus (HAstV), norovirus (NoV), and adenovirus (AdV). Phylogenetic analyses of the targeted virus genes were performed. In Turkey, viruses were detected in 87/150 samples (58%), which included 69 (79.3%) with single viruses and 18 (20.7%) with multiple viruses. AdV was the most common virus, followed by HBoV. In Bangladesh, viruses were detected in 123/138 samples (89.1%), which included 29 (23.6%) with single viruses and 94 (76.4%) with multiple viruses. NoV GII was the most common, followed by AdV. The dominant genotypes among the virus species were HBoV 2A, HAstV 1, NoV GI type 1, and AdV 40. For NoV GII, the Hunter variant of genotype 4 in Turkey and genotype 17 in Bangladesh were the most common among the sequenced strains. It was concluded that the distribution of the viruses associated with diarrhea in Turkish and Bangladeshi children was different. Enteric viruses and mixed infections were more prevalent in Bangladesh than in Turkey. J. Med. Virol. 86:1159–1168, 2014. © 2013 Wiley Periodicals, Inc.